Innovation in production and digital marketing of herbal medicine to enhance quality and sustainability of the Tirta Sari Herbal Group in Magelang - Wardani, Arief Kusuma; Lestari, May Synta; AzZahra, Anindya Shafira; Yusriyyah, Aanisah (Community Empowerment, 2025)
This activity aims to improve the quality of Tirta Sari herbal medicine products through innovations in production processes and digital marketing. Innovations include the use of appropriate technology, such as temperature control during production, and promoting products via Instagram. Temperature variation testing was conducted to extend product shelf life without altering taste. As a result, the fresh herbal medicine produced was more hygienic, with extended shelf life—3 days for beras kencur and 7 days for kunir asam. Additionally, partners gained a better understanding of the importance of hygiene and food safety. Digital marketing via Instagram has helped the products become more widely recognized and favored by the public.